Optimalisasi Kinerja Karyawan PT Global Pratama Powerindo: Pengaruh Kepuasan Kerja Dan Lingkungan Kerja Fisik - Romadani, Putra Umar Makrup; Prabowo, Juddy (Universitas Islam Kadiri, 2024)
The study conducted at PT. Global Pratama Powerindo reveals that job satisfaction plays a crucial role in enhancing employee performance. However, the physical work environment, when considered independently, does not significantly impact employee performance, as indicated by non-significant statistical results. Interestingly, when analyzing the combined influence of job satisfaction and the physical work environment, a noteworthy impact on employee performance is observed. The F-test results demonstrate that the amalgamation of these factors collectively contributes significantly to enhancing employee performance. Approximately 58% of the variability in employee performance can be explained by job satisfaction and the physical work environment, as indicated by the coefficient of determination (R2) test. The remaining 42% of variations may be influenced by unexamined factors. The research highlights the reliability of the measurement instruments used, ensuring the credibility of the findings. The practical implications suggest that PT. Global Pratama Powerindo's management can improve policies and strategies by focusing on optimizing job satisfaction and the physical work environment to elevate employee performance. Despite valuable insights, the study acknowledges limitations, including a restricted sample size and a narrow industry sector focus, encouraging future research with broader samples and diverse industry involvement. Overall, the research contributes significantly to understanding the dynamics influencing employee performance in the renewable energy sector.